Proceso de atención de enfermería en paciente de 16 años con miocardiopatía periparto y shock séptico. - Aucancela Toapanta, Hellen Brigitte (2020)
Peripartum cardiomyopathy is a rare disease; However, it presents a high mortality rate, rising even more when diagnosis and treatment are not carried out early, it is a disorder of unknown cause, in which left ventricular dysfunction and symptoms of heart failure occur between the last month of pregnancy and the first five months after delivery, in women without pre-existing signs or symptoms of heart disease. Septic Shock is a type of shock that occurs as a result of a generalized inflammatory response of the body due to an infection, it is a sepsis, in which the disorders of the cardiovascular, metabolic and cellular systems are so deep that it increases in a Mortality is significant, among the first infectious foci to which severe sepsis and septic shock have been attributed, is pneumonia, followed by intra-abdominal infections, urinary tract infections and primary infections of the bloodstream. I present the case of a 16-year-old puerperal woman, referred from the Guaranda Hospital, admitted to the area of the Maternal Intensive Care Unit after vaginal delivery plus postpartum hemorrhage and Hellp's syndrome complicated by peripartum cardiomyopathy and septic shock due to pulmonary focus. Breathing with mechanical ventilatory support due to a patent tracheostomy and presents episodes of thermal rise intermittently. It is determined that the nursing care process is an essential tool where care is prioritized in a logical and systematic way that is of vital importance for the recovery of the patient.